Peningkatan Kesiapan dan Self-Efficacy Nelayan Relawan Siaga Bencana Berbasis Masyarakat (SIBAT) melalui Health Coaching Hands-Only CPR dalam Penanganan Awal Near Drowning di Kelurahan Malabero,Kota Bengkulu - Desi Susilawati; Bardah Wasalamah; Nova Yustisia; Imron Rosyadi (Institut Kesehatan Suaka Insan, 2026)
Non-fatal drowning is a life-threatening emergency that commonly occurs among fishermen in open water environments. One of the most critical emergency interventions is cardiopulmonary resuscitation (CPR). This study aimed to analyze the effect of health coaching based on Hands -Only CPR on the readiness and self-efficacy of Siaga Bencana Berbasis Masyarakat (SIBAT) volunteers. The research used a quasi-experimental pretest-posttest control-group design with 36 respondents, selected through purposive sampling. Data were analyzed using the paired t-test and the Mann-Whitney test. The results showed a significant improvement in both self-efficacy and readiness after the intervention (p=0.000). The mean self-efficacy score increased from 61.83 to 75.61, while readiness improved from 53.81 to 68.36. Furthermore, the intervention group demonstrated significantly higher scores compared to the control group (p<0.05). In conclusion, health coaching based on Hands-Only CPR is effective in improving the readiness and self-efficacy of SIBAT Volunteers in the management of near-drowning cases.